Methods of Teaching Dutorbas Instrumental Performance in Children's Music and Art Schools on the Basis of New Modern Pedagogical Technologies (Eurasian Journal of Learning and Academic Teaching, 2022)
This article discusses the design of pedagogical technologies for music culture lessons and the effective organization of the lesson. The technology of using the Dutorbas tool is discussed in the article.